Assisted Suicide: Do We Own Our Bodies? - Tarkki, Jarmo (Dialog, 2004)
The ethics of physician-assisted suicide is explored here in light of classic philosophical discussions of the ownership of one's body plus biblical discussions of the relationship of body and soul. Motives for individual and group suicide are brought to bear on bioethical principles such as that of autonomy. Ethical analysis is here challenged by the case of a 91 year-old woman, Ragnhild, who lived after professional judgments that her life should be ended.